GENETIC DIVERSITY OF IRAQI LOCAL COWS AND THEIR COMPARISON WITH IMPORTED COWS USING MICROSATELLITE MARKERS - S. M. Al-Jub; Riyadh Hamad senkal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to identify the genetic diversity of microsatellite markers CSSM66, ETH10 and ILSTS34 using 100 cows of several breeds distributed as follows: 30 local Iraqi cows (equally divided into Restaki, Janoubi and Sharabi) as well as  50 Holstein cows (German) and 20 Brahman bulls after amplification in PCR reaction, 16 alleles of ETH10, CSSM66 and ILSTS34 markers were detected in a sample of studied cattle and they were 7, 6 and 5 alleles, respectively. The total Shannon (I) was 1.5400, and it was found that the average value of Obs_Hom is smaller than the average value of Exp_Het, being 0.2600 and 0.7544, respectively. This indicates the presence of high genetic heterogeneity or diversity among cows. The average values ​​of FIS, FIT and FST and genetic migration Nm -0.6257, -0.0162, 0.3749 and 0.4168, respectively. These results showed through the UPGMA tree a common ancestry between domestic cattle and Brahman.